BRIDGING TECHNOLOGICAL GAP AMONG ENGLISH TEACHERS THROUGH DIGITAL SQUAD PROJECT - Nia Kurniawati (University of Kuningan, 2018)
The technology advancement has forced the teachers ignoring their generation to migrate from off line into digital platform since the use of technology in education has changed the face of education massively. This project tried to capture an effort in bridging the technology gap among teachers across generation by forming a digital squad to provide digital teaching media assistance to teachers. It consists of several English education pre-service students in a private university who have high interest and skill on technology. This study explored the facts on the squad activities, the teacher participants’ responses to the events organized by digital squad, and the obstacles in conducting the project. The results showed that the workshops organized by the squad gained positive feedback from the teacher participants. However, the classic problems frequently appear during the activities involving technology are the internet connection and the various technological competence among the participants. Finally, it is suggested to employ younger generation to bridge the technology gap among language teachers across generation in education setting, since the younger generation is usually techno savvy and the older generation should be willing to embrace the technology development in order to survive in millennial classroom.Keywords: digital squad; workshop; language teachers; generation; technology; teaching media.